Renal artery thrombosis and hypertension in a 13 year old girl with antiphospholipid syndrome. Issue 3 (March 1990) - Ostuni, P A; Lazzarin, P; Pengo, V; Ruffatti, A; Schiavon, F; Gambari, P
Abstract : The case of a 13 year old girl with renal artery thrombosis and hypertension is described. A cerebrovascular accident and a probable occlusion of the superior mesenteric artery also occurred. Very high levels of 'lupus anticoagulant', anticardiolipin antibodies as well as false positive Venereal Disease Research Laboratory tests were repeatedly shown. Moreover, the patient fulfilled at least four classification criteria for systemic lupus erythematosus, but only a slight positivity for antinucleolar antibodies was present. The striking relation between antiphospholipid antibody levels and clinical events and the treatment of this complex syndrome are discussed.